UTILIZATION OF LABORATORIES AND EDUCATIONAL SERVICES AND THEIR INFLUENCE ON STUDENTS' MATERIAL MATERIAL MASTERY - Norbertus Adrianus Ribu Hipir; Yayah Rahyasih; Taufani Chusnul Kurniatun (CV. TOTUS TUUS, 2026)
Rapid developments in science and technology demand that schools optimize learning facilities and educational services to improve students’ mastery of learning materials. In many junior high schools, especially in developing and border areas, laboratories and educational services are available but not always utilized optimally. This study aims to analyze the influence of laboratory utilization (computer and science laboratories) and educational services on students’ material mastery in junior high schools across Raimanuk District, Belu Regency. Employing a quantitative ex post facto research design, data were collected through questionnaires administered to 100 teachers selected using proportional random sampling from a population of 133 teachers in six junior high schools. The data were analyzed using multiple regression analysis to examine both partial and simultaneous effects of the independent variables on students’ material mastery. The results indicate that laboratory utilization has a positive and significant effect on students’ mastery of learning materials. Educational services also show a significant positive influence, and jointly both variables contribute meaningfully to explaining variations in students’ material mastery. These findings suggest that practical learning experiences supported by structured and responsive educational services enhance students’ conceptual understanding. In conclusion, this study highlights that improving learning outcomes requires not only the availability of laboratories but also their effective utilization and integration with quality educational services. The study contributes scientifically by reinforcing an integrative perspective on educational infrastructure and services as complementary determinants of learning quality.